Haemonchus contortus: A multiple-resistant Brazilian isolate and the costs for its characterization and maintenance for research use - Chagas, Ana Carolina S.; Katiki, Luciana M.; Silva, Ives C. [UNESP]; Giglioti, Rodrigo [UNESP]; Esteves, Sérgio N.; Oliveira, Márcia Cristina S.; Barioni Jr., Waldomiro (Elsevier, 2013)
The aim of this work was to determine the resistance level of Haemonchus contortus isolated from the Santa Inês flock of the Embrapa (Brazilian government's Agricultural Research Company), Southeast Livestock Unit (CPPSE), as well as to determine costs of characterizing and maintaining this isolate in host donors. Forty-two male Santa Inês lambs were experimentally infected with 4000 H. contortus infective larvae of the field isolate of CPPSE, called Embrapa2010, and divided into six treatment groups, which received triclorfon, albendazol plus cobalt sulfate, ivermectin, moxidectin, closantel and levamisole phosphate, as well as a negative control group (water). Egg per gram (EPG) counts were performed at 0, 3, 7, 10 and 14. days post treatment when the animals were slaughtered for parasite count. The data were analyzed using the RESO statistical program, considering anthelmintic resistance under 95% of efficacy. EPG and worm count presented a linear and significant relation with 94% determination coefficient. The susceptibility results obtained by RESO through both criteria (EPG and worm count) were equal, except for closantel, showing that the isolate Embrapa2010 is resistant to benzimidazoles, macrocyclic lactones and imidazothiazoles. The need of a control group did not appear to be essential since the result for susceptibility in the analyses with or without this group was the same. Suppression in egg production after treatment did not occur in the ivermectin and moxidectin groups. In the control group, the establishment percentage was just 12.5 because of the low number of third-stage larvae, resistance (innate and infection immunity) of the animals studied plus good nutrition. Drug classes presented similar efficacy between adults and immature stages. The costs for isolate characterization were calculated for 42 animals during 60. days. The total cost based on local market rates was approximately US$ 8000. The precise identification of Brazilian isolates and their establishment in host donors would be useful for laboratorial anthelmintic resistance diagnoses through in vitro tests, which has an annual cost of approximately US$ 2500 for maintenance in host donors. © 2012 Elsevier B.V.
Keywords: Gastrointestinal nematodes; Host donor; Isolate; Resistance; Small ruminants; albendazole; benzimidazole; closantel; cobalt sulfate; diantel; ivermectin; levamisole; macrolide; metrifonate; moxidectin; neguvon; tetramisole; unclassified drug; valbazen10 cobalto; animal experiment; animal model; Brazil; controlled study; cost; data analysis; drug resistance; egg production; feces analysis; female; haemonchosis; Haemonchus contortus; innate immunity; lamb; larva; male; nonhuman; priority journal; worm; Animals; Anthelmintics; Costs and Cost Analysis; Drug Resistance, Multiple; Female; Haemonchiasis; Haemonchus; Male; Parasite Egg Count; Research; Sheep; Sheep Diseases; Animalia; Nematoda; Ovis aries